Do Goal-Free Problems with Guided Questions Affect Retention, Transfer, and Cognitive Load? - Aprillia, Fika; Retnowati, Endah (Edumatica : Jurnal Pendidikan Matematika, 2025)
This study aimed to examine the effects of problem presentation and guided questions on students’ retention, transfer, and cognitive load. The study used a 2×2 factorial design with two factors: problem presentation (goal-free vs. goal given) and guided questions (with vs. without). The subjects consisted of 150 seventh-grade students from a public junior high school in Sleman Regency, who were randomly assigned to four experimental groups. The instruction was carried out in three phases: introduction, acquisition, and testing. Data were analyzed using two-way ANOVA at a significance level of 0.05. The results showed that problem presentation did not have a significant effect on retention and transfer but had a significant effect on cognitive load. Guided questions did not have a significant effect on any of the dependent variables. A significant interaction was found between problem presentation and guided questions on retention, transfer, and cognitive load in the retention test. Goal-given problems were more effective without guided questions for improving retention and transfer, while guided questions were more effective when combined with goal-free problems. Cognitive load on the retention test was higher for goal given problems with guided questions because goal given problems and guided questions led to means-end analysis and deep information processing.